Osman Lins: ruptura e inovação em avalovara - Pereira, Marcio Roberto [UNESP] (2010)
In this article we analyze how the character of the story-teller is build up as a fictional creation in the novel Avalovara (1973) by Osman Lins (1924-1978).We associated the building process of the narrator-character to the poetic wich brings a fragmentary feature to the writer’s language, and reflects a search for some coherency in a given chaotic environment, wherein space itself becomes the role of a dialogue between identity and representation of the real in the construction of the narrative analyzed here.